IMPACT OF YOGA ON STRESS AND WEIGHT OF MENOPAUSAL WOMEN - DR.B.JAYABHARATHI, M.SC (N), PH.D , YIC, DYT, (International Journal of Pharma and Bio Sciences, 2016)
Menopause is a normal occurrence in the life of every woman. This study aimed to assess the impact of yoga on stress and weight of menopausal women. The study was conducted in selected villages at Kattankulathur Block, Chennai. Simple random sampling technique was adopted to select 260 menopausal women (130 in study group and 130 in control group). The study group received yoga training programme (Yogasanas, pranayama and meditation) and they practiced yoga for 18 weeks. Assessments were made by Sheldon Cohen’s Perceived Stress Scale and ISO certified weighing scale. After 18 weeks, the stress was reduced to a greater extent in study group than in control group at p= 0.001 level. The mean weight reduction was 3.58 from the base line weight in study group. This study concluded that yoga is an effective intervention in reducing the stress level and managing the weight of menopausal women.